Československá vojenská mise v Kanadě: Činnost a výsledky - Tomáš Jiránek (Theatrum Historiae)
The Czechoslovak military mission in Canada (1941–1943) aimed to secure the enlistment of local Czechs to Czechoslovak units in Great Britain. The original expectations regarding the number of men who could be enlisted were overoptimistic; in just under 2 years only 147 men were sent to Europe. There were various reasons for this: overreliance on the patriotism of the emigrants, the younger generation of which no longer had strong links with the mother country and who often enlisted in the Canadian army; the late launch of the recruitment drive; enemy propaganda from the Slovak Hlinka Guard and the Nazis; and the fact that Czech settlements were spread all over Canada. Similar problems were also faced by representatives of other European nations that had come to Canada for the same purpose.